Dinamika Promosi dalam Era Global - Arrasyid, Abduh Malik Ahmad; Wahyuni, Erika Sri; Suhairi, Suhairi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this study is to tell or educate readers about the global promotion dynamics. This study employs a quantitative literature review as its type of research. The research method involves combining data from multiple sources, such as books and the internet, into a single one. Finding the necessary information is the method that is used to collect the data. Human thinking and behavior can be altered by rapid technological advancement, particularly in marketing mix strategies like advertising, customer promotion, personal selling, and publicity. The promotion of goods and services has seen a rapid rise in the use of technology and informatics systems like the internet and cyberspace. Manufacturers can use this opportunity to inform, offer, persuade, motivate, and even